Genotypic and phenotypic characterization of antimicrobial resistance in Salmonella strains isolated from both No-Antibiotics-Ever (NAE) and conventional broiler complexes - Yagya Adhikari; Dianna V. Bourassa; Sabin Poudel; Matthew A. Bailey; Richard J. Buhr; Kenneth S. Macklin (Poultry Science)
Antimicrobial resistance is a serious global public health concern that could endanger the efficacy of antibiotics used for the treatment of diseases in humans, animals, and plants. The objective of this study was to characterize the antimicrobial resistance (AMR) pattern of Salmonella strains isolated from different stages of both No-Antibiotics-Ever (NAE) and conventional integrated broiler complexes. ResFinder was used to identify AMR genes from whole genome sequences while the phenotypic resistance of 14 different antibiotics was determined using broth microdilution method. Odds ratio and 95 % confidence limits were calculated using multivariate logistic regression for different complexes and stages of broiler production (α = 0.05). The major AMR genes identified were aac(6′)-Iaa, aph(6)-Id, aph(3″)-Ib, blaCARB-2, sul1, tet(A), tet(B), tet(G), floR, fosA7, gyrA, and parC. The phenotypic results showed that 58 % (49/85) of isolates were resistant to at least one antibiotic class (AOR), 24 % (20/85) of isolates were resistant to at least two or more classes of antibiotics (ATR) and 6 % (5/85) of isolates were multi-drug resistant (MDR). In terms of 14 different antibiotics tested, 41 %, 39 %, 6 %, 5 % and 2 % of isolates were resistant to sulfisoxazole, tetracycline, nalidixic acid, ampicillin and ciprofloxacin respectively. Interestingly, 80 % (32/40) of Kentucky isolates showed phenotypic resistance to either tetracycline or sulfisoxazole or both. In addition, the odds of ATR Salmonella detection were 7 times (1.37 – 43.45; 95 % CL) more likely in the isolates from NAE complex as compared to conventional broiler complex (p = 0.0233). Overall, drug-resistant Salmonella were present within and surroundings of poultry production and poultry product that could potentially contaminate the final raw product. It may lead to complicated antimicrobial therapy during foodborne infections in consumers.